F(-5)= 3-2(-5)
= 3+10
= 13
Hope it helps :))
Answer:
(x+4)
Step-by-step explanation:
You have to distribute the exponent of 4 to the whole equation.
so step one is to distribute to the 3
3^4= 81
then we have to distribute to the x
x^4
then to the 2
2^4= 16
81 * x^4 * 16
* = multiplication sign
Identify the steps that complete the proof.
♣ = <span>✔ vertical angles theorem</span>
♦ = <span>✔ SAS</span>
♠ = <span><span>✔ CPCTC</span></span>
12,500 divide 1999, 12,500 divide 1998, etc hope this helps